Ocular Manifestations in Patients Undergoing Maintenance Hemodialysis - A Cross Sectional Study - Prerna Arjyal Kafle; Neha Priyadarshini Chaudhary; Nancy Goyal; Naphibanroi Lamar (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Chronic kidney disease (CKD) patients undergoing maintenance hemodialysis (HD) are at risk of a wide range of ocular manifestations, often underdiagnosed but potentially vision-threatening. In Nepal, the increasing burden of diabetes and hypertension has amplified the need to understand ocular comorbidities. The objective of this study was to assess the prevalence and spectrum of ocular findings among patients undergoing maintenance hemodialysis and evaluate their association with systemic comorbidities. MATERIAL AND METHODS A descriptive, cross-sectional study was conducted at the Department of Ophthalmology, Birat Medical College Teaching Hospital. A total of 147 adult patients on maintenance HD were enrolled. Ophthalmic examination including visual acuity, slit-lamp, intraocular pressure, and fundus assessments were performed. Data were analyzed using SPSS version 22, and associations were tested using the chi-square test (p < 0.05 considered significant). RESULTS Of the 147 patients, 76.1% were aged ≥40 years and 69.4% were male. The mean duration of dialysis was 2.75 ± 1.69 years. Ocular manifestations were present in 76.87% of patients, with the most common findings being hypertensive retinopathy (57.8%), dry eyes (57.1%), cataracts (24.5%), and non-proliferative diabetic retinopathy (23.1%). Statistically significant associations were found between hypertension and hypertensive retinopathy (p = 0.002), and between diabetes (especially combined with hypertension) and diabetic retinopathy (p = 0.005). CONCLUSION A high prevalence of ocular abnormalities was observed among patients undergoing maintenance hemodialysis, often without symptoms. Routine ophthalmic screening should be integrated into nephrology care to enable early detection and prevent irreversible vision loss.